When nature continues to surprise: observations of the hectocotylus of Argonauta argo, Linnaeus 1758. Issue 1 (1st January 2021) - Battaglia, P.; Stipa, M. G.; Ammendolia, G.; Pedà, C.; Consoli, P.; Andaloro, F.; Romeo, T.
Abstract: In this paper, a live hectocotylus, found inside a stranded female Argonauta argo shell, allowed us to describe the behaviour of this copulatory arm and add new information on its morphology. The hectocotylus penile filament is contained in a special membranous pocket or sac, almost completely transparent, extending from the apex of the basal part to about one-third of the central section. The hectocotylus assumes a folded position to protect the penile filament in the membranous sac. This is probably extracted only when copulation occurs. Our observations seem to suggest that the shell may have the secondary function of storing and protecting the hectocotyli received by males until the copulation. The observations confirmed the high vitality and endurance of the hectocotylus after detachment from the A. argo male.